(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The need for fiscal decentralization is due to the need to overcome centrifugal economic trends in the country in Ukraine. At the same time, the implementation of fiscal decentralization in Ukraine, along with the positive ones, revealed some problems that are important to study and correct in the light of world experience, especially the EU countries, as this is a necessary step in view of the European integration course of our country. First of all, it concerns the overcoming of centrifugal tendencies in the more developed regions of Ukraine, which requires studying the experience of EU countries in solving this problem. Based on this experience, it is important to put the state’s revenues and expenditures under the strict control of the public of the regions in order to overcome corruption in the higher echelons of the Ukrainian authorities. To solve this problem, it would be expedient to consolidate existing regions and introduce a bicameral parliament in Ukraine, for example, in many countries of the world. The limit for the redistribution of state (public) finance between the center and the regions of Ukraine in the coming years should be the proportion of 50 to 50%, with the increase in 2020 in the ratio of 35 to 65% in favor of local budgets. When developing a new mechanism for distributing taxes and expenditures between the center, regions and enlarged communities of Ukraine, it is necessary to develop such measures that would allow the latter to obtain additional tax opportunities for financing additional expense powers. For this purpose it is important to leave at the level of certain regions a certain part of the VAT, and at the level of the united territorial communities to half of the income tax. A fiscal problem for many regions of Ukraine is that most local governments and newly formed united territorial communities do not have the appropriate financial resources for efficient use of resources. Therefore, with the further reformation of united territorial community finances, it is necessary to develop a mechanism for the interconnection of regional financial funds and relevant united territorial community funds to address these problems.